A lightweight verifiable outsourced decryption of attribute-based encryption scheme for blockchain-enabled wireless body area network in fog computing. (February 2020) - Guo, Rui; Zhuang, Chaoyuan; Shi, Huixian; Zhang, Yinghui; Zheng, Dong
Wireless body area network includes some tiny wearable sensors for monitoring the physiological data of user, which has been a promising method of promoting the quality and efficiency greatly in healthcare. The collected physical signs are aggregated into the medical documents and uploaded to cloud server for utilizing by the remote user. As these files are highly sensitive privacy data, there is a vital challenge that constructs a secure and efficient communication architecture in this application scenario. Based on this standpoint, we present a lightweight verifiability ciphertext-policy attribute-based encryption protocol with outsourced decryption in this article. Specifically, our construction enjoys the following six features: (1) Although the outsourced decryption enables to save the computation overhead of the data user sharply in an attribute-based encryption scheme, the ciphertext is out of control and the correctness cannot be guaranteed by the data owner. The proposal provides the verifiability of ciphertext that ensures the user to check the correctness efficiently. (2) The size of the ciphertext is constant that is not increased with the complexity of attribute and access structure. (3) For Internet of Things devices, it introduces the fog computing into our protocol for the purpose of low latency and relation interactions, which has virtually saved the bandwidth. (4) With the help of blockchain technique, we encapsulate the hash value of public parameter, original and transformed ciphertext and transformed key into a block, so that the tamper-resistance is facilitated against an adversary from inside and outside the system. (5) In the standard model, we prove that it is selectively chosen-plaintext attack-secure and verifiable provided that the computational bilinear Diffie–Hellman assumption holds. (6) It implements this protocol and shows the result of performance measurement, which indicates a significant reduction on communication and computation costs burden on every entity in wireless body area network.